Makna Rezeki dalam Ayat-Ayat Al-Qur'an (Kajian Tafsir Ibnu Katsir) - Zubaedah, Siti (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
If humans understand well what the meaning of sustenance is, then they will live their lives with obedience and happiness, but on the contrary, it is feared that humans will fall into the wrong understanding which then has a bad impact on themselves. The author is interested in expressing the word sustenance in the verses of the Qur'an using the book of interpretation of the Qur'an al-Azim or better known as the book of Tafsir Ibn Kasir by Sheikh al-Imam al -Hafiz Abu al-Fida 'Imanuddin Isma'il bin Umar bin Kasir al-Quraish al-Dimasyq because Ibn Kasir's commentary is one of the most famous books of interpretation of bil ma'sur in writing his commentary has the method that is in accordance with what Ibn Kas says in his book "the most reliable method of knowledge is the verse of the Qur'an with the verse of the Qur'an (munasabah), if you cannot confirm the Qur'an with the Qur'an Qur'an, then try to use the Prophet's words and if they don't find it in the Qur'an, they will lead to an opinion because the Companions better know the context and conditions that only they witnessed, besides that they also have a clear understanding. perfect, true knowledge and good deeds but if not found Also, most of the Imams refer to the previous tabi'in and scholars."